Impact of inventory allocation policies on downstream supply variability in a two-echelon system. (1st January 2013) - Niranjan, Suman; Ciarallo, Frank W.
This paper studies the impact of inventory allocation policies on the downstream supply variance and total cost in a two-echelon system with multiple sources of demand. We introduce a new metric known as the supply coefficient of variability (SCV) that will aid managers in the process of selecting inventory allocation policies in the presence of multiple sources of demand. We find that the variance in the supply is significantly affected by the inventory allocation polices used at the upstream node. We further find that the optimal inventory levels at each node in a multi-echelon system are not only a function of the demand, capacity, and lead time, but also a function of the allocation policy employed. A simulation-based inventory optimisation (SIO) algorithm is developed to search for optimal base-stock levels for a two-echelon system based on derivative estimates from an infinitesimal perturbation analysis (IPA) framework.